دراسة تركيز النترات والنتريت في الخيار المنتج في البيوت البلاستيكية في محافظة طرطوس وانعكاسه على صحة الإنسان - سليمان غياث حيدر; سلمان عصام عز الدين (Latakia University Journal -Medical Sciences Series, 2013)
تناولنا في هذه الدراسة خطورة زيادة تركيز النترات والنتريت في الخيار المنتج من البيوت البلاستيكية في طرطوس, فجمعنا بصورة عشوائية 100 عينة خيار من 50 بيت بلاستيكي من منطقة سهل عكار في طرطوس من عشرة قرى (المدحلة , أرزونة , تل سنون, عين الزبدة , بيت شوفان , شاص , الرياف , زاهد , الدكيكة , حبرون ) من كل قرية 5 بيوت بلاستيكية , وتم تعبئة استمارة خاصة عن كل بيت بلاستيكي تحوي المساحة , كمية السماد المعدني , كمية السماد العضوي , مصدر مياه الري مع تحليل النترات والنتريت فيها بواسطة جهاز Colorimeter , وتم الكشف عن التلوث بالنترات والنتريت بمنتج الخيار بواسطة جهاز <a href="http://www.google.com/url?sa=t&rct=j&q=%D8%B5%D9%88%D8%B1+%D8%AC%D9%87%D8%A7%D8%B2+%D8%B3%D8%A8%D9%83%D8%AA%D8%B1%D9%88%D9%81%D9%88%D8%AA%D9%88%D9%85%D8%AA%D8%B1&source=web&cd=20&ved=0CHAQFjAT&url=http://alataco.maktoobblog.com/427107/&ei=wzqhULPnDo2W0QWWooDIAw&usg=AFQjCNFNSK6jZ994_gSo006nAisL3fgNQA">Spectrophotometer , أظهرت النتائج أن تركيز النترات كان مرتفعاً بشكل واضح في عينات الخيار في قرية الرياف 615.29 ملغ/كغ وزن رطب , وأقله في تل السنون 126.15 ملغ/كغ وزن رطب, وكان تركيز النتريت عالياً في قرية الرياف أيضاً 0.06ملغ/كغ وزن رطب , وأقله في عينات قرية بيت شوفان 0.023 ملغ/كغ وزن رطب, مع وجود فروقٍ معنوية واضحة جداً بين تركيز النترات والنتريت في عينات الخيار (p=0.000). عند مقارنة النتائج مع الحد المسموح به حسب منظمة الصحة العالمية كانت نسبة العينات الملوثة في بيوت قرى الرياف والمدحلة وعين الزبدة 100%, وفي قرية بيت شوفان 90%, وفي قريتي حبرون والدكيكة 80% , وفي قرى أرزونة وشاص وزاهد 60% وفي قرية تل السنون 30% , ونسبة التلوث العامة بكل عينات الخيار 76%. وكانت كل تراكيز النتريت بالخيار ضمن الحد المسموح به أقل من 1 ملغ/كغ . This study addresses the issue of the danger of the high amount of Nitrates and Nitrites found in Cucumbers grown in greenhouses in the coastal region in Tartous, Syria . One hundred samples of greenhouse Cucumbers (in their green state) were collected at random from 50 Greenhouses (2 samples from each Greenhouse) in ten villages in Sahil Akkar in Tartous. The villages are: Arzona, Madihli, A. Zibdi, B. Shofan, Shas, Riyaf, Zahid, Dkaiki, Habroun and T. Sunoun. Five Greenhouses were selected from each village. A special information card was prepared for each greenhouse which included the area of the greenhouse, the type of fertilizers used in it, and the source of water used to irrigate the house. The water was tested by a device known as Colorimeter. Another device called Spectrophotometer was used to test the amount of Nitrates and Nitrites found in Cucumbers. The results show that the highest amount of Nitrates was in the samples taken from Riyaf (615.29 mg/kg, and the lowest amount in the samples from T.Sunoun (126.15 mg/kg. The Nitrites were at their highest also in Riyaf at 0.06 mg/kg and at their lowest in the samples of B. Shoufan at 0.023 mg/kg. The results also show variation in the Probability value (P=0.000) in the Cucumbers samples. When comparing the amounts reported by the World Health Organization (WHO), it was found that the amounts of Nitrates and Nitrites ranged between 100% in Riyaf, A. Zibdi and Madhli, followed by 90% in B.Shoufan, and 80% in Habroun and Dkaiki,and 60% in Arzona, Zahid,. and Shas ,and 30% in T. Sunoun . The percentage of contamination in all the Greenhouses reached only 76%whole. the concentration of the Nitrites was within the standard level, less than 1%mg/kg.